Letman : the artwork and lettering of Job Wouters. - Frieling, Gijs; Klanten, Robert; Letman (Berlin : Gestalten, 2012)
This book is the first monograph from Amsterdam-based illustrator Job Wouters, who works under the pseudonym Letman. In addition to commissioned designs for publications including New York Times Magazine, Playboy, It’s Nice That, and Creative Review and brands such as Audi, Heineken, Dries Van Noten, Tommy Hilfiger, Eastpak, and Universal, Letman also includes a compelling selection of his personal projects and sketches.
boek